The emergence of the Omani Arab press in Zanzibar (1329 AH - 1383 AH / 1911 AD - 1964 AD ) (Journal of Misan Researches, 2023)
The Arabic press was known in Zanzibar as a cultural product that emerged during the era of Sayyid Barghash bin Said after the emergence of the Royal Press (1867–1887 AD and 1287-1305 H) that is considered one of the oldest journals in East Africa at that time. When these newspapers were initiated, each of them had cultural orientations and specific political dimensions that came as a result of several facts and successive events, and the political and social transformations in that era, which had the most significant role in achieving national unity, spreading Arab culture and the teachings of the Islamic religion, and enlightening the minds of the people in general. Through the articles and news published in them, a group of scholars and intellectuals who had a clear impact on segments of society took over these newspapers.As a result, the study's significance lies in exploring the most important Omani Arab newspapers that originated in Zanzibar, the factors that influenced their emergence since 1911, and addressing the types of issues that the newspapers focused on: acknowledging that they paid great attention to various social and political issues, and that Omani and international issues have a place in their pages, as this era of Zanzibar history is a crucial period full of eveThrough the importance of the study, it aims to track the factors that led to the emergence of the Omani Arab newspapers in Zanzibar. These most important newspapers appeared, what sources the newspapers relied on to investigate their news, and to seek the role that these newspapers played in enlightening the minds of the public about the issues taking place in Zanzibar, especially the issue of rooted national unity that Britain was trying to destabilize as it was under British protection.To achieve the objectives of the study, it is necessary to follow the historical descriptive and analytical method to monitor the aspects related to the factors of the emergence of Arab newspapers in Zanzibar, to list the most important newspapers, and to track the type of issues raised in them.            This study is divided into introduction, three major axes, and conclusion. The introduction deals with a brief background on the history of the world press. The first axis focuses on the factors of the emergence of journalism in Zanzibar. The second axis lists the most important Omani Arab newspapers that originated in Zanzibar. The third axis deals with the most important sources that were relied on by newspapers to report their stories. Finally, the study ends with a conclusion that summarizes the findings and the recommendations of the study.